2021
DOI: 10.1152/japplphysiol.00343.2021
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose and skeletal muscle tissue DNA, RNA, and protein content

Abstract: This investigation studied DNA, RNA, and protein contents of adipose and skeletal muscle tissues from young active individuals. A series of optimization steps were investigated to aid in determining the optimal approach to extract high-yield and high-quality biomolecules. These findings contribute to the knowledge gap in adipose tissue requirements for molecular biology assays, which is of increasing importance due to the growing interest in adipose tissue research involving human exercise physiology research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
5
1
Order By: Relevance
“…Other critical variables also influenced the quality of the RNA, namely, the condition of the tissue or the impact of degradation during processing steps. The vulnerability of RNA in rat ILMs is in contrast to findings that characterize skeletal muscle mRNA as highly stable relative to the liver, brain, and adipose tissue [12][13][14] . This suggested that variable RNA stability across species, tissue types, and organ layers may require modified extraction strategies according to the specimen and sample size.…”
contrasting
confidence: 63%
See 2 more Smart Citations
“…Other critical variables also influenced the quality of the RNA, namely, the condition of the tissue or the impact of degradation during processing steps. The vulnerability of RNA in rat ILMs is in contrast to findings that characterize skeletal muscle mRNA as highly stable relative to the liver, brain, and adipose tissue [12][13][14] . This suggested that variable RNA stability across species, tissue types, and organ layers may require modified extraction strategies according to the specimen and sample size.…”
contrasting
confidence: 63%
“…integrity restricted the downstream assessment to a low-throughout application and perturbed the RT-qPCR performance. In contrast, living tissue samples following human muscle biopsy yielded between 456 to 676 ng total RNA and 7.9 ± 0.6 RIN 12 . Unfortunately, compared to other soft tissue types, the distinctive ILMs have not been amenable to RNA-Seq due to differences in cell characteristics 14 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Obtained values for RNA range from 20 to 280 ng/mg for different methods in this study are similar to those from skin, heart, or prostate and significantly lower than tissues like muscle, liver, or pancreas. The average DNA yield ranges from 70 to 428 ng/mg for methods compared in this study, which makes it several times less than the yield obtained from muscle, liver, lung, or thymus ( Walker et al, 2016 ; Liska & Ruprecht, 1999 ; Biase et al, 2002 ; Ginzberg, Kafri & Kirschner, 2015 ; Stroh et al, 2021 ). Broad ranges of nucleic acid yield are mainly a result of the capabilities of the techniques used.…”
Section: Discussionmentioning
confidence: 86%
“…The least degraded DNA samples were also achieved with spin-column methods, although additional homogenization in liquid nitrogen (method IV) may cause higher degradation. Method III gives a higher DNA yield (340.70 (284.60–394.70) ng/mg) than the spin-column method tested by Stroh et al (2021) , which used homogenization with a disposable plastic pestle and DNeasy Blood & Tissue kit (52 ± 14 ng/mg.). The A260/280 ratio for method III is 1.83 (1.80–1.83), which is exactly in the desired range when A260/280 for the technique used by Stroh et al (2021) is slightly above (2.4 ± 0.2).…”
Section: Discussionmentioning
confidence: 98%